(untitled) (Fiep Bulletin - online, 2015)
Introducion:The malnutrition affects the acting of several organic systems directly however, the effect can be several in each organ or tissues, in agreement with the importance of the same for the organism. The heart miocytes can suffer structural alterations under those conditions, modulating the heart performance during the physical activity. Objective: Analysis of the morphometric alterations of the ventricular miocytes in nuclear level, starting from the calculation of the nuclear volume pondered medium, as well as the coefficient cardiac weight /body weight of animals submitted to a aproteic diet. Methodology: Wistar Albino rats were used, males and female, born of nurtured female rats and undernourished, divided in: group control (N): animals (n=5) maintained in proteic diet and the undernourished group (D): animals (n=5) maintained in diet of low calorie (5% protein) and killed to the 21 days of age. The animals and their respective hearts were heavy and their prepared ventricles for analysis under microscopy of light second record histomorphometric. The images were obtained through the program Axiovision and analyzed by the method proposed by GUNDERSEN (1988). Results: The body and heart weights were shown decreased in the undernourished ones however the coefficient heart weight /body weight didn’t present significant difference among the 2 groups. The histomorphometrical analysis revealed a nuclear increase in the undernourished animals in relation to the controls. Conclusion: The obtained data denote a direct interference of the diet of low calorie in the corporal and heart mass; however the relationship between body weight and heart weight was not altered. The increase in the nuclear volumes appears for a preservation of the heart function.